MANAJEMEN PONDOK PESANTREN DALAM MENJAWAB TANTANGAN MODERNITAS Studi Multisitus di Pondok Pesantren Lirboyo dan Pondok Pesantren Al-Falah Kediri - Moh. Irsyad Fahmi M.R. (LP2M IAIN Tulungagung, 2017)
Pesantren in the face of change required to do contextualization without sacrificing their original character as a social and religious educational institutions. Boarding schools must fix his weaknesses, namely by applying good management education. Updates made to the functioning boarding schools so that the role and contribution as a community development players seem real. Thus, boarding the future is expected not only play its traditional functions but should be more than that schools should do the transformation that can support the quality of human resources (HR) is certainly inward beyond boarding schools and continuing the development and community development. Adaptive capabilities boarding on the times it will strengthen its presence as well as showing its superiority. These advantages lies in the ability of schools combining intellectual, emotional, and spiritual.